HEALTH(CARE) AND THE TEMPORAL SUBJECT - Davies, Ben (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2018)
Many assume that theories of distributive justice must obviously take people’s lifetimes, and only their lifetimes, as the relevant period across which we distribute. Although the question of the temporal subject has risen in prominence, it is still relatively underdeveloped, particularly in the sphere of health and healthcare. This paper defends a particular view, “momentary sufficientarianism,” as being an important element of healthcare justice. At the heart of the argument is a commitment to pluralism about justice, where theorizing about just principles demands paying attention to the role particular goods play in our lives. This means that different approaches to the temporal subject—as well as other relevant issues—may be appropriate for different goods, including different goods within healthcare. In particular, the paper discusses two central goods targeted by healthcare: life-saving and pain relief. The view is offered as complementary to, rather than competitive with, lifetime approaches. As such, the paper finishes by considering how a pluralist approach, which engages both with people’s lives as a whole and with their states at particular moments, can reconcile the potentially competing claims in healthcare that emerge from these two perspectives.